Aleppo and its hinterland in the Ottoman period = Alep et sa province à l'époque ottomane - Winter, Stefan; Ade, Mafalda (Social, economic and political studies of the Middle East, 2020)
Inhaltsverzeichnis: 1. Les Turkmènes d'Alep à l'époque ottomane (1516-1700) / Enver Çakar -- 2. Armenians in the Production of Urban Space in Early Modern Judayda, Aleppo / Elyse Semerdjian -- 3. Patterns of Leadership in the Guilds of 17th-Century Aleppo / Charles L. Wilkins -- 4. Alep et l'émirat du désert (çöl beyliği) au XVIIe-XVIIIe siècle / Stefan Winter -- 5. Halabis and Foreigners in Aleppo's Mediterranean Trade: The Role of Levantine Merchants in Eighteenth-Century Commercial Networks / Mary Momdjian -- 6. The Millet Wars in Aleppo, 1726-1821: An Ottoman perspective / Bruce Masters -- 7. Antioche sous l'occupation égyptienne (1832-1840) : l'émergence d'un centre de pouvoir militaire et modernisateur / Sylvain Cornac -- 8. L'innovation judiciaire dans l'Empire ottoman : l'établissement d'un tribunal de commerce à Alep au milieu du XIXe siècle / Mafalda Ade -- 9. Disciplining Disobedient Subjects: The Punishment of Aleppo's Insurgents in 1850 as a Contentious Issue / Feras Krimsti -- 10. Les consuls Picciotto et Poche, intermédiaires des intérêts belges à Alep (1855-1914) / Nicolas Jodoin -- 11. Entre réseaux régional et transrégional : La Mawlawiyya dans la province d'Alep au XIXe siècle / Stefan Knost -- Index/Indexe.